Evaluation of Bare Rooted Transplanting Methods of Kinnow Mandarin for Enhanced Field Establishment - Srivastava, A. K.; Bhan, Chander; Bairwa, S. K. (International Journal of Bio-resource and Stress Management, 2022)
An experiment was carried out at the Department of Horticulture, Agricultural Research Station, Sriganganagar under the S. K. Rajasthan Agricultural University, Bikaner, Rajasthan, India during July to October and February to April months of 2014−15 and 2015−16. The objective of the study was to evaluate the feasibility of the bare root transplanting method with the optimum time to establish Kinnow mandarin seedlings. The findings of the study revealed that bare rooted Kinnow mandarin seedlings can be successfully transplanted in the month of August to October during the monsoon period and February to March during the spring months with 94–96% transplanting success. Transplanting at 48 hours after packaging was reported 91% establishment success whereas, it was 87% at 72 hours after the bare rooted packaging. However, the highest transplanting success (100%) was noted with polythene bag plants (intact soil) followed by bare rooted buddlings treated with IBA 200ppm plus Carbendazim 0.1% plus Defoliation which was recorded as 97% success. In the control treatment, it was recorded minimum with 76 percent transplanting success.